Anti-tumor Activity of Propofol: A Focus on MicroRNAs - Ashrafizadeh, Milad; Ahmadi, Zahra; Farkhondeh, Tahereh; Samarghandian, Saeed (Current Cancer Drug Targets, 2020)
Background: MicroRNAs are endogenous, short, non-coding RNAs with the length as low as 20 to 25 nucleotides. These RNAs are able to negatively affect the gene expression at the post-transcriptional level. It has been demonstrated that microRNAs play a significant role in cell proliferation, cell migration, cell death, cell differentiation, infection, immune response, and metabolism. Besides, the dysfunction of microRNAs has been observed in a variety of cancers. So, modulation of microRNAs is of interest in the treatment of disorders. Objective: The aim of the current review is to investigate the modulatory effect of propofol on microRNAs in cancer therapy. Methods: This review was performed at PubMed, SCOPUS and Web of Science data-bases using keywords “propofol’, “microRNA”, “cancer therapy”, “propofol + microRNA” and “propofol + miR”. Results: It was found that propofol dually down-regulates/upregulates microRNAs to exert its antitumor activity. In terms of oncogenesis microRNAs, propofol exert an inhibitory effect, while propofol significantly enhances the expression of oncosuppressor microRNAs. Conclusion: It seems that propofol is a potential modulator of microRNAs and this capability can be used in the treatment of various cancers.
Keywords: pharmacological targeting